2020
DOI: 10.1108/bij-01-2020-0019
|View full text |Cite
|
Sign up to set email alerts
|

Technology management for innovation in organizations: an argumentation-based modified TISM approach

Abstract: PurposeIn the rapidly changing business world, innovation plays a vital role for organizations to gain a competitive advantage. Various factors associated with technology management and innovations in organizations are diverse in the existing literature. Therefore, there is a need to bridge these gaps in the fitting proportions toward innovations within organizations. The primary objective of this study is to identify, explain and interpret the relationships between the identified technology-related factors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 117 publications
0
25
0
1
Order By: Relevance
“…Crawford (2005) found a strong link between leadership (transformational) and KM because leaders encourage information acquisition, creation and application. Similarly, top management ensures effective KM and resource allocation to boost productivity and innovation processes (Rajan et al, 2021). Top management also promotes organizational effectiveness, KM and team learning to stimulate innovation within the firms (Masa'deh et al, 2016).…”
Section: 3mentioning
confidence: 99%
“…Crawford (2005) found a strong link between leadership (transformational) and KM because leaders encourage information acquisition, creation and application. Similarly, top management ensures effective KM and resource allocation to boost productivity and innovation processes (Rajan et al, 2021). Top management also promotes organizational effectiveness, KM and team learning to stimulate innovation within the firms (Masa'deh et al, 2016).…”
Section: 3mentioning
confidence: 99%
“…Therefore, TISM is used to articulate ill-defined and unclear models into well-defined and clear models (Sushil, 2017; Yadav and Sushil, 2014; Singh and Sushil, 2013). The m-TISM (Sushil, 2017; Bamel et al , 2019; Rajan et al , 2020; Dhir et al , 2021) is the extension of TISM (Sushil, 2012) to the knowledge of interrelationships, the degree of association and the logic behind relationships.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the modified Total Interpretive Structural Modelling (m-TISM) is used to develop the model. This approach is the upgraded version of TISM and ISM (Rajan et al , 2020). The ISM is the qualitative analysis-based approach that provides the hierarchical model which generally referred as the well-defined model (Warfield, 1977; Kumar et al , 2017), whereas in the TISM the interpretation is done for every identified variable that further presents the model (digraph) based on iterations (Mittal et al , 2016, 2017; Sindhwani and Malhotra, 2017).…”
Section: Methodsmentioning
confidence: 99%